Study on 60 cases of common bile duct stone, there different modality of management and its inference - Ahirwar, Sovat Lal (International Surgery Journal, 2020)
Background: The aim of the study was to determine the best treatment modality for common bile duct stone become more challenging as large number of options available such as endoscopic, laparoscopic or open surgical methods, we need to choose specific therapy according to patient’s clinical conditions, and individual expertise. Methods: It is prospective study including 60 patient having common bile duct stone along with gall bladder stone, its different modality of management and its inference, conducted in Bhopal Memorial Hospital and Research Centre, Bhopal, during period of January 2017 to January 2020. Results: In 60 cases 41 patients undergoes to endoscopic retrograde cholangio pancreatography (ERCP) first, stone successfully removed in 34 patients and stent placed, one patients developed pancreatitis after ERCP, managed conservatively, In 6 patients retained stone after ERCP procedure, one patients developed surgical emphysema after procedure, managed with ICD and conservatively, and one patient had bleeding during sphincterotomy so its procedure abandoned and one of the patient failed to cannulate common bile duct (CBD). 21 patients undergo laparoscopic common bile duct explorations, 2 lap CBD exploration converted to open CBD exploration with cholecystectomy, due to adhesion at hepatocystic triangle. Five patients undergoes open CBD exploration, in one patient hepaticojejunostomy was done as patient was having CBD stone with stricture. No mortality during and after procedure. Conclusions: Management of CBD stone is depends upon individual expertise and available modality. If surgeons are expertise then lap CBD exploration with cholecystectomy without attempting to ERCP guide stone removal is best approach in majority of patients.